Serum Zinc Level in Preterm Low Birth Weight Babies and Its Comparison between Preterm AGA and Preterm SGA Babies (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):145-8.The abstract of this article is available on the PubMed website